Features of pharmacognosy problems in world religions - Shaxzod Azamovich Mirzaev; Sherzod Farxodovich Majidov (Science and Education, 2025)
The paper examines the interrelationships of pharmacology and world religions, as well as the peculiarities of attitudes towards natural medicines in Buddhism, Christianity and Islam, which have not lost their significance to the present day.